Accès aux financements externes et pérennité de la très petite entreprise: quelle évidence en temps de crise sécuritaire?. (2nd January 2023) - Djoutsa Wamba, Léopold; Koye, Romuald
Abstract: The Far North of Cameroon has been weakened since 2014 by recurring attacks and suicide bombings orchestrated by the Islamic sect 'Boko-Haram'. This article aims to analyse the moderating effect of this security crisis on the relationship between access to external financing by VSBs in their start-up phase and their sustainability. The data needed to conduct the study were collected, with a questionnaire, from 229 promoters of VSBs created between 2014 and 2018 and still operating in the Far North region of Cameroon. These data were then analysed using the logistic regression model. The results demonstrate a positive effect of access to external financing during the start-up phase of the VSB on its sustainability. However, it appears that the frequency of Boko-Haram attacks and the restrictive measures adopted by the government (border closures and curfews) are not conducive to the external financing of the VSB, let alone its sustainability. This result shows that the intensification of the security crisis experienced by all micro-entrepreneurs, combined with the challenges specific to their activity, has thus undermined the confidence they place in the future prospects of their business.